2003
DOI: 10.1161/01.hyp.0000050928.96979.a5
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Renal Blood Flow in Patients With Moderate to Severe Hypertension

Abstract: Abstract-It is generally assumed that renal blood flow is symmetric in the absence of renal artery stenosis. The aim of the present study was to evaluate whether this is really the case. From a group of consecutive hypertensive patients who had undergone renal angiography, we selected those with patent renal arteries. In all of them selective renal blood flow (RBF) measurements ( 133 Xenon washout technique) had been performed with blood sampling from aorta and both renal veins (nϭ148). Asymmetry of RBF, defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Van Onna and co-authors showed that asymmetry of renal blood flow was present in up to 51% of hypertensive patients. Moreover, mean left renal blood flow was on average significantly lower than the right mean renal blood flow (van Onna et al, 2002). Similar, Caralps et al reported that in 10 out of 11 asymmetry cases the left kidney was more affected than the right one (Caralps et al, 1974).…”
Section: Discussionmentioning
confidence: 95%
“…Van Onna and co-authors showed that asymmetry of renal blood flow was present in up to 51% of hypertensive patients. Moreover, mean left renal blood flow was on average significantly lower than the right mean renal blood flow (van Onna et al, 2002). Similar, Caralps et al reported that in 10 out of 11 asymmetry cases the left kidney was more affected than the right one (Caralps et al, 1974).…”
Section: Discussionmentioning
confidence: 95%
“…only discernable by an asymmetry in left to right RBF, already affects renal regulation of blood pressure [77]. The other aspect involves both the stenotic and the contralateral kidney: enhanced actions of ANG II will lead to sodium retention directly and indirectly due to aldosterone formation, with increased extracellular fluid volume as a consequence.…”
Section: Special Case: Renal Artery Stenosismentioning
confidence: 99%
“…Yet, it might have important consequence for the development of cardiovascular disease, because van Onna et al reported an asymmetry of renal blood flow in patients with moderate to severe hypertension. 23 Sympathetic hyperinnervation and vascular smooth muscle hyperplasia may be involved in the development of hypertension in experimental animals 24,25 and possibly humans. 26 Previous studies from our own group in the chicken embryo demonstrated that chronic moderate hypoxia results in a sympathetic hyperinnervation of the arterial system.…”
Section: Sanders Et Al Intrauterine Stress and Renal Development 1287mentioning
confidence: 99%